STRATEGI PENGEMBANGAN IDENTITAS DAN PENINGKATAN BRAND AWARENESS PADA UMKM LOYAL SNACK MELALUI SOSIAL MEDIA - Putra, Edy Yulianto; Vanessa, Vanessa (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This internship was conducted at UMKM Loyal Snack, a small business specializing in cheese sticks since 2017, which has primarily operated through offline sales and telephone orders without a strong brand identity or digital presence. The aim of this internship was to develop the brand identity and increase brand awareness of Loyal Snack by implementing digital marketing strategies. The research methods included observation, interviews with the business owner, and documentation of promotional activities and customer interactions. The strategies applied involved creating a logo and slogan, establishing TikTok and Instagram social media accounts, and managing WhatsApp Business as a communication and promotional channel. Additionally, promotions through Instagram Ads in the form of stories and posts, as well as creating a Linktree link to facilitate access to all digital platforms, were implemented. The results showed a significant increase in brand recognition, enhanced customer engagement, and expanded market reach. Digital marketing proved to be an effective solution to overcome marketing challenges faced by UMKM and foster business growth in the digital era